The next big thing : innovations for a better, smarter, stronger tomorrow - Marciano, Rob; Trefil, James, 1938- (National Geographic, 2026)
"What will our future look like? In The Next Big Thing, meteorologist and science reporter Rob Marciano invites readers to take a journey through the innovations that will change our lives for the better in four key realms of science: Energy - How will we power the planet? Marciano ventures inside a nuclear fusion reactor to learn about sustainable, near-infinite energy. Electricity - Marciano goes airborne in an electric one-person aircraft--could be tomorrow's Uber! Infrastructure - Can we build cleaner cities? Marciano visits Ascent, a timber skyscraper in Milwaukee. Information - Is AI friend or foe? Marciano meets android SOPHIA and asks her that question. Complementing Marciano's reporting, physicist James Trefil unpacks the science behind each innovation and highlights other promising developments: solid-state batteries, quantum computers, 3-D printed homes, and robots." -- Provided by publisher.